2014
DOI: 10.1210/jc.2013-1707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bazedoxifene/Conjugated Estrogens on the Endometrium and Bone: A Randomized Trial

Abstract: BZA/CE showed low rates of endometrial hyperplasia and improved lumbar spine and total hip BMD and was generally safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 25 publications
3
102
0
Order By: Relevance
“…A new strategy for ER modulation, known as tissue selective estrogen complex (TSEC), combines estrogen therapy (conjugated equine estrogens) with bazedoxifene. Data from clinical trials indicate that this association leads to improvements of menopausal symptoms and bone mass, without causing adverse effects on the breast and uterus (116)(117)(118)(119)(120). However, the anti-fracture and cardiovascular effects of this association have not been adequately investigated yet.…”
Section: Selective Estrogen Receptor Modulatorsmentioning
confidence: 99%
“…A new strategy for ER modulation, known as tissue selective estrogen complex (TSEC), combines estrogen therapy (conjugated equine estrogens) with bazedoxifene. Data from clinical trials indicate that this association leads to improvements of menopausal symptoms and bone mass, without causing adverse effects on the breast and uterus (116)(117)(118)(119)(120). However, the anti-fracture and cardiovascular effects of this association have not been adequately investigated yet.…”
Section: Selective Estrogen Receptor Modulatorsmentioning
confidence: 99%
“…Most clinicians use raloxifene for the management of osteoporosis in patients with contraindications to other antiresorptive agents or for the treatment of women desirous of breast cancer prevention in whom enhanced skeletal health would be an additional Clinical Therapeutics benefit. 58 Of note, the third-generation SERM bazedoxifene in combination with conjugated estrogens 59 was recently approved by the US Food and Drug Administration (FDA) for the prevention of postmenopausal osteoporosis.…”
Section: Estrogen/selective Estrogen Receptor Modulatorsmentioning
confidence: 99%
“…In one 12-month trial, the incidence of endometrial hyperplasia and bleeding with Duavive was similar to that observed with placebo and it was not associated with breast tenderness. 2 There is little clinical experience of Duavive in women aged over 65 years, it is not recommended for women with renal impairment and it is contraindicated in those with hepatic impairment. Other prescribing cautions and contraindications are similar to those of other HRT preparations.…”
Section: Propertiesmentioning
confidence: 99%